(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
A study schedule is one of the basic educational needs. When it, however, becomes an automated requirement, it will be more complicated and harder to solve and distribute study lectures without considering the restrictions and limitations imposed to create study schedules as these constraints differ according to the importance of each constraint and the extent to which it can be applied to reach the optimal solution. There is a dozen of methods and algorithms used in the process of study schedules, and these methods differ according to their results. In this research, we used the genetic algorithm and we achieved distinctive results that can be trusted for a real institution to generate an automated study schedule with free-conflict lectures based on the constraints list we set for this approach.